2020
DOI: 10.1039/d0nr00834f
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surface roughness on the adhesive interactions and phase behavior of suspensions of calcite nanoparticles

Abstract: Nanoparticle roughness influences the adhesive interactions between calcite nanoparticles inhibiting the formation of gel phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…In addition, particles with smoother surfaces feature strong adhesive forces. 44 The nitrogen adsorption–desorption linear isotherms of untreated ground eggshell particles, PCC in the presence of PSS polyelectrolyte with low salt molar concentration and a silver loaded calcium carbonate are shown in Fig. 8C .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, particles with smoother surfaces feature strong adhesive forces. 44 The nitrogen adsorption–desorption linear isotherms of untreated ground eggshell particles, PCC in the presence of PSS polyelectrolyte with low salt molar concentration and a silver loaded calcium carbonate are shown in Fig. 8C .…”
Section: Resultsmentioning
confidence: 99%
“…Simulations of NP-membrane interactions show that NP surface roughness greatly minimizes repulsive interactions, thereby promoting adhesion. [30,31] In the present work, hydrophilic and hydrophobic 100 nm quasi-spherical (AuNSPs) and star (AuNSTs) shape AuNPs were synthesized to explore the antibacterial mechanism of non-translocating AuNPs as a function of size, shape, and surface charge. [5,32] The surface charge and chemical properties of the NPs were determined by capping agents which play a crucial role in controlling the interactions between bacteria and the NPs (Figure 3).…”
Section: R Rn =mentioning
confidence: 99%
“…Simulations of NP–membrane interactions show that NP surface roughness greatly minimizes repulsive interactions, thereby promoting adhesion. [ 30,31 ]…”
Section: Figurementioning
confidence: 99%
“…Indeed, computational studies have shown that NPs transition from an associated percolating gel to a dissociated fluid phase when surface roughness is incorporated. 36 To investigate the effects of roughness, we also obtained the MFEP of atomically corrugated "rough" nanocubes as introduced earlier. Fig.…”
Section: Effect Of Surface Roughnessmentioning
confidence: 99%